Belajar Tuntas - Rusmin B., Muhammad (Inspiratif Pendidikan, 2016)
In the process of mastery learning, there are many things that should be considered in order the designed activities can be run successfully. They are; 1) the specific teaching objectives and the selecting materials that are relevant and appropriate to the learning activity; 2) the teaching and learning approach that allows each individual can learn; 3) giving and the use of feedback and remedial; 4) setting standards for students’ mastery before proceeding to the next learning process; and 5) assessing learning achievement based on Benchmark Reference Assessment and not on Norm Reference Assessment.